Performance audit: A cross-country comparison of practices of selected supreme audit institutions - Monika Vasiliauskienė; Dalia Daujotaitė (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This study aims to present the conceptual framework of performance audits impact that support our investigation of the process of selection performance audit topics at Supreme audit institutions (SAIs) level. The results of the study include the technique for choosing performance audit topics used by the Lithuanian SAI and the SAI of the Netherlands. The data were gathered using case studies and semi-structured in-depth interviews with the field experts. The results of the study demonstrated a range and the complexity of the arguments underlying the selection of the topic for performance audits: there are no mandatory requirements or standards governing the process; therefore, every SAI chooses its own path. Each SAI applies specific performance audit topics selection methods determined by their original long-term practical experience. Selecting right topics for performance audit is a task of crucial importance for each SAI. Gathering information about all areas and making a decision where to perform an audit is an important part of strategic research efforts. Data collection is a lengthy process that takes place throughout the year. Each SAI has a framework for strategic and annual planning that has clearly set deadlines, uses a transparent qualified and/or quantified approach to ranking risks/audit proposals, and is based on the criteria relating to materiality, topicality, feasibility and added value.
Keywords: M42; M48; 650; supreme audit institutions; performance audit; audit topics; impact; case study